If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -9) = (x + 3) Reorder the terms: 4(-9 + x) = (x + 3) (-9 * 4 + x * 4) = (x + 3) (-36 + 4x) = (x + 3) Reorder the terms: -36 + 4x = (3 + x) Remove parenthesis around (3 + x) -36 + 4x = 3 + x Solving -36 + 4x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -36 + 4x + -1x = 3 + x + -1x Combine like terms: 4x + -1x = 3x -36 + 3x = 3 + x + -1x Combine like terms: x + -1x = 0 -36 + 3x = 3 + 0 -36 + 3x = 3 Add '36' to each side of the equation. -36 + 36 + 3x = 3 + 36 Combine like terms: -36 + 36 = 0 0 + 3x = 3 + 36 3x = 3 + 36 Combine like terms: 3 + 36 = 39 3x = 39 Divide each side by '3'. x = 13 Simplifying x = 13
| 6(2z-3)-2z=-5(z-2)+2 | | (2x-y)-16i=10+4yi | | 1/3(21-3a)=6-a | | 4ln(x-3)=0 | | 4x-7=3x-5 | | 5p-5=2p+4 | | 7(e+3)-4e=4(e+6)+1 | | 8x-3=2(x-1) | | 9+8x=86+5 | | -9(4y-7)=3-5y | | 6(x+5)=3(2x+5)+15 | | 8e+16=5e-17 | | 5(x-4)=2(2x+5) | | 3x+10=2x+10 | | (x+1)(x-5)(x-7)=0 | | f+(-3)=9 | | 2y=-5y-49 | | -14+y=2 | | -4(t-3)-2(-7t-8)=9(t+2)+4 | | 36(x-144)=72 | | 15x+26-2x=6x+61 | | b-2=11 | | 5x=-5x+10 | | 3-4q=-5+8q | | 7y^3+5y^2= | | -4(t-3)-2(7t-8)=9(t+2)+4 | | 11x-2y+12w-6y-2w+2x= | | 9h+7-6h=-5+9 | | 6-2(3x-2)=14 | | 1/2(w+1)=9 | | 6a^2x^2+11a^2x+4a^2= | | 4v-2(3-v)=-13 |